2012
DOI: 10.1016/j.ultrasmedbio.2011.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Dispersion Measures Liver Steatosis

Abstract: Crawling waves, which are interfering shear wave patterns, can be generated in liver tissue over a range of frequencies. Some important biomechanical properties of the liver can be determined by imaging the crawling waves using Doppler techniques and analyzing the patterns. We report that the dispersion of shear wave velocity and attenuation, that is, the frequency dependence of these parameters, are strongly correlated with the degree of steatosis in a mouse liver model, ex vivo. The results demonstrate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 45 publications
11
96
0
Order By: Relevance
“…A recent study of excised mouse livers showed that liver steatosis correlates with shear wave dispersion (a property related to tissue viscosity) but not liver elasticity (16), which implies that viscosity may provide independent information about tissue state in addition to elasticity. An MR elastography study in 88 patients (14) showed that both elasticity and viscosity correlate with liver fibrosis stage; however, viscosity had less predictive value than elasticity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of excised mouse livers showed that liver steatosis correlates with shear wave dispersion (a property related to tissue viscosity) but not liver elasticity (16), which implies that viscosity may provide independent information about tissue state in addition to elasticity. An MR elastography study in 88 patients (14) showed that both elasticity and viscosity correlate with liver fibrosis stage; however, viscosity had less predictive value than elasticity.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of liver tissue elasticity were obtained by six sonographers (with 8,11,11,15,16, and 25 years of experience) in the right lobe of the liver by using a curvilinear transducer (C5-1, Philips Healthcare) through intercostal spaces with the subject lying supine with right arm abduction. The operator positioned the probe by using real-time B-mode imaging to locate a large liver area free of major vessels.…”
Section: Us Measurementsmentioning
confidence: 99%
“…Huwart et al (2007) studied 88 patients by MR elastography and concluded that the elasticity appeared to be a more discriminant marker for liver fibrosis staging. Barry et al (2012) showed that viscosity may be associated more closely with another tissue pathological state-liver steatosis, which is an accumulation of fat in the liver. In this study, Barry concluded that increasing the amounts of fat evidently increased the liver viscosity, which resulted in increased dispersion of shear wave speed and attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…ARFI parameters, shear wave velocity, and attenuation are strongly correlated with the degree of HS in animal studies [33], [34]. With human samples, studies have shown that HS has no statistical influence [35] or correlation [32] with ARFI results, in contrast to Fibroscan [32], [35], [36].…”
Section: Discussionmentioning
confidence: 99%